Polylactide cocrystals and gels. (10th December 2022) - Praveena, N. M.; Akhila, N. S.; Gowd, E. Bhoje
Abstract: Synthetic biodegradable polyesters have emerged as an alternative to conventional petroleum‐derived polymers for a diverse range of applications. Among these, polylactides are the most commercially successful biodegradable polymers. The presence of stereoregular chains makes poly(l ‐lactide) (PLLA) and poly(d ‐lactide) (PDLA) semicrystalline. The blending of enantiomeric PLLA and PDLA resulted in the stereocomplex formation due to non‐covalent interactions of enantiomeric chains. PLLA exhibits different crystalline forms depending on the crystallization conditions with different chain conformations, as well as different chain packing structures. PLLA and its blend with PDLA are known to form cocrystals with certain solvents. This review focuses mainly on the recent progress in understanding the cocrystal formation, polymorphic phase transitions of these cocrystals, gelation mechanism and stereocomplex formation in blend gels of polylactides. Abstract : Crystallization conditions of amorphous/mesophases and interconversions between various crystalline forms of poly(l ‐lactide).